IFN-γ-independent control of M. tuberculosis requires CD4 T cell-derived GM-CSF and activation of HIF-1α. - Erik Van Dis; Douglas M Fox; Huntly M Morrison; Daniel M Fines; Janet Peace Babirye; Lily H McCann; Sagar Rawal; Jeffery S Cox; Sarah A Stanley (PLoS Pathogens)
The prevailing model of protective immunity to tuberculosis is that CD4 T cells produce the cytokine IFN-γ to activate bactericidal mechanisms in infected macrophages. Although IFN-γ-independent CD4 T cell based control of M. tuberculosis infection has been demonstrated in vivo it is unclear whether CD4 T cells are capable of directly activating macrophages to control infection in the absence of IFN-γ. We developed a co-culture model using CD4 T cells isolated from the lungs of infected mice and M. tuberculosis-infected murine bone marrow-derived macrophages (BMDMs) to investigate mechanisms of CD4 dependent control of infection. We found that even in the absence of IFN-γ signaling, CD4 T cells drive macrophage activation, M1 polarization, and control of infection. This IFN-γ-independent control of infection requires activation of the transcription factor HIF-1α and a shift to aerobic glycolysis in infected macrophages. While HIF-1α activation following IFN-γ stimulation requires nitric oxide, HIF-1α-mediated control in the absence of IFN-γ is nitric oxide-independent, indicating that distinct pathways can activate HIF-1α during infection. We show that CD4 T cell-derived GM-CSF is required for IFN-γ-independent control in BMDMs, but that recombinant GM-CSF is insufficient to control infection in BMDMs or alveolar macrophages and does not rescue the absence of control by GM-CSF-deficient T cells. In contrast, recombinant GM-CSF controls infection in peritoneal macrophages, induces lipid droplet biogenesis, and also requires HIF-1α for control. These results advance our understanding of CD4 T cell-mediated immunity to M. tuberculosis, reveal important differences in immune activation of distinct macrophage types, and outline a novel mechanism for the activation of HIF-1α. We establish a previously unknown functional link between GM-CSF and HIF-1α and provide evidence that CD4 T cell-derived GM-CSF is a potent bactericidal effector.